1917-1977 - Dolgorukov, Nikolai Andreyevich (Плакат СССР (Plakat), 1977)
Drawing of Lenin in profile among panels showing armed workers, Red cavalry and panicking capitalists, Battleship Aurora firing ray of light, Red Army soldier looming over Hitler and Reichstag. signing of peace treaty with flags of Warsaw pact countries and Cuba, Soviet ship smashing into small boat waving NATO flag, and Soviet citizens standing triumphant with red flags and banners PO-0588